A 3D anthropometric sizing analysis system based on North American CAESAR 3D scan data for design of head wearable products. (March 2018) - Lee, Wonsup; Lee, Baekhee; Yang, Xiaopeng; Jung, Hayoung; Bok, Ilgeun; Kim, Chulwoo; Kwon, Ochae; You, Heecheon
Highlights: 2299 heads of the Civilian American and European Surface Anthropometry Resource (CAESAR) were edited for measurement. 30 anthropometric head and face dimensions were measured. A 3D Anthropometric Sizing Analysis System (3D-ASAS) was developed and applied in head-wearable product design. A sizing system of a head-wearable product can be easily found by product designers through simple use of the 3D-ASAS. Abstract: The present study developed a sizing analysis system for head-related product designs based on the Civilian American and European Surface Anthropometry Resource (CAESAR) database of North Americans. A total of 2299 heads in the CAESAR database were manually edited and 26 anthropometric landmarks were marked on the edited 3D heads to measure 30 anthropometric dimensions related to head-related product designs. The 3D anthropometric sizing analysis system (3D-ASAS) developed in the study provides analysis functions of a sizing system and representative face models by considering a target product, a target population, the number of size categories, and key anthropometric dimensions based on the CAESAR head measurements. Further research to reduce the efforts of manual editing and landmarking of 3D body scan data is discussed for efficient application of the 3D-ASAS to the design process of various wearable products.